Design of Phage-Cocktail–Containing Hydrogel for the Treatment of Pseudomonas aeruginosa–Infected Wounds - Fatemeh Shafigh Kheljan; Farzam Sheikhzadeh Hesari; Mohammad Sadegh Aminifazl; Mikael Skurnik; Sophia Goladze; Gholamreza Zarrini (Viruses, 2023)
Recently, the treatment of infected wounds has become a global problem due to increased antibiotic resistance in bacteria. The Gram-negative opportunistic pathogen Pseudomonas aeruginosa is often present in chronic skin infections, and it has become a threat to public health as it is increasingly multidrug resistant. Due to this, new measures to enable treatment of infections are necessary. Treatment of bacterial infections with bacteriophages, known as phage therapy, has been in use for a century, and has potential with its antimicrobial effect. The main purpose of this study was to create a phage-containing wound dressing with the ability to prevent bacterial infection and rapid wound healing without side effects. Several phages against P. aeruginosa were isolated from wastewater, and two polyvalent phages were used to prepare a phage cocktail. The phage cocktail was loaded in a hydrogel composed of polymers of sodium alginate (SA) and carboxymethyl cellulose (CMC). To compare the antimicrobial effects, hydrogels containing phages, ciprofloxacin, or phages plus ciprofloxacin were produced, and hydrogels without either. The antimicrobial effect of these hydrogels was investigated in vitro and in vivo using an experimental mouse wound infection model. The wound-healing process in different mouse groups showed that phage-containing hydrogels and antibiotic-containing hydrogels have almost the same antimicrobial effect. However, in terms of wound healing and pathological process, the phage-containing hydrogels performed better than the antibiotic alone. The best performance was achieved with the phage–antibiotic hydrogel, indicating a synergistic effect between the phage cocktail and the antibiotic. In conclusion, phage-containing hydrogels eliminate efficiently P. aeruginosa in wounds and may be a proper option for treating infectious wounds.